The Impact of the Digital Transformation of Public Services on Administrative Court Disputes at the Administrative Court - M. Aldo Dellano; M. Zahran Al-Gibran; Naila Syafa Azzahra; Ravie Surya Justico; Taufiq Alamsyah (Journal of Human Interaction and Social Studies, 2026)
The digital transformation of public service delivery through the Electronic-Based Government System (SPBE) has significantly altered the structure of administrative governance and the legal characteristics of State Administrative Decisions in Indonesia. This study examines the implications of digital transformation for administrative disputes before the Administrative Court and evaluates the adequacy of existing legal frameworks in addressing emerging challenges associated with electronically generated governmental actions. Employing a normative legal research design, the study utilizes statutory, conceptual, and doctrinal approaches based on primary legal sources, including administrative, electronic information, and constitutional regulations, as well as relevant scholarly literature. The analysis demonstrates that electronic administrative decisions possess legal legitimacy as reviewable administrative acts; however, their implementation generates complex juridical issues concerning evidentiary standards, attribution of administrative responsibility, algorithmic decision-making, and procedural accountability. Existing procedural and substantive legal frameworks provide partial accommodation for digital governance but remain insufficient to address the evolving realities of technologically mediated administrative action. The study argues that harmonization of administrative law, electronic governance regulation, and procedural adjudication standards is necessary to strengthen legal certainty, judicial protection, accountability, and the effectiveness of administrative justice in the digital era.